Left atrial remodeling in heart failure: coexistence and additive prognostic power of atrial dilation and dysfunction. (25th November 2020) - Rossi, A; Carluccio, E; Cameli, M; Inciardi, R; Mandoli, G.E; D'Agostino, A; Biagioli, P; Pugliese, N.R; Pastore, M.C; Maffeis, C; Mengoni, A; Dini, F.L
Abstract: Background: Heart failure (HF) is associated with volumetric and functional changes of left atrium (LA). Purpose: It is still unclear whether the two atrial abnormalities necessarily coexist and if they have additive prognostic implications. Methods: 690 patients with HF due to reduced left ventricular ejection fraction (EF) formed the study population. Each patients underwent comprehensive echocardiographic evaluation; atrial function was assessed by means of strain analysis during reservoir (PALS). End-point of the study was overall survival free of hospitalization. Results: Patients were divided in 4 groups according to left atrial size (34 ml/mq) and function (PALS 20%). 64 patients (10%) were characterized by completely normal left atrium (group 1), 150 (25%) by dilated LA by normal PALS (group 2), 130 (20%) by normal LA volume but abnormal PALS (group 3) and 200 patients with dilated LA and decreased PALS (group 4). Clinical and echocardiographic characteristics of the groups are presented in the table. Decreased PALS was associated with worse survival both in patients with normal and abnormal LA volume (p<0.0001 for each group). Conclusions: Increased volume and decreased function of LA frequently but not necessarily coexist. LA functional impairment affects prognosis independently of LA volume. Funding Acknowledgement: Type of funding source: None